Preeclampsia Basic, Genomic, and Clinical (Comprehensive Gynecology and Obstetrics,, 2018)
This volume is an excellent guide that comprehensively illustrates hypertensive disorders of pregnancy, especially preeclampsia, in both the basic and clinical aspects. Preeclampsia is a pregnancy-specific multi-organ disorder and a leading cause of maternal and neonatal mortality. The pathophysiology of pregnancy-specific disorders was long unknown, but recently many new findings have been reported from the point of view of pathophysiology. Furthermore, this complication of pregnancy, especially preeclampsia, is a potent risk factor for chronic conditions such as cardiovascular disease, diabetes mellitus, kidney disease, and hypertension. The book is composed of seven parts including genetic background, pathology, pathophysiology, and the latest prediction and treatment of preeclampsia. Specific basic topics such as immunological maladaptation, placental adenosine signaling, and new prediction markers are also expounded by experts. Thus it benefits not only obstetricians, pediatricians, nephrologists, diabetologists, and cardiologists, but also immunologists, endocrinologists, geneticists, pathologists, biologists, and molecular biologists who are interested in the treatment of hypertension in pregnancy.